Recontextualização do currículo de ciências naturais no 2º ciclo do ensino fundamental - Silva, Edson Gonçalves da (2013)
This research is part of the Master's Degree in Education PPGE / IE / UFMT on Line School Organisation Research, Training and Practice School, and is linked to the Curriculum Research Group, Training and School Practice - GPCFOPE. The guiding question arises on the following question: how teachers recontextualize the curriculum of natural sciences in the 2nd round of state schools in Cuiaba - MT? Based on this question, this research aims to understand how the policy cycles of state schools Mato Grosso as teachers recontextualize the curriculum of natural sciences in the 2nd cycle. The fabric of the theoretical contributions is given by Bernstein (1996), Ball (1992), Lopes (2005, 2008); Mainardes (2007) and Tura (2009) on the theme recontextualization. Concerning the Formation Cycles has dialogue by reference organization for scholars of cycles: Arroyo (1999, 2004), Fernandes (2011) Krug (2001); Fetzner (2007), Lima (2002) and Mainardes (2006, 2007 , 2009), and on the curriculum of Natural Sciences and Scientific Literacy, Chassot (1995, 2003, 2004, 2007, 2008, 2011), Krasilchik (1987, 1992, 1996), Macedo (2004). Curricular issues on the theoretical underpinning: Silva (1999), Saul (1992), and Silva Moreira (1994), Goodson (1997), Sacristan (2000), Macedo (2006) and Macedo Lopes (2011). The methodological approach is qualitative interpretative approach, with a cycle of policies formulated by Ball and colleagues (BOWE et al. 1992, Ball, 1994). Research subjects are 06 (six) teachers who teach Natural Sciences in the 2nd cycle and pedagogical staff composed of two (02) officers and 02 (two) educational coordinators of two (02) schools organized by education and training courses in public schools Cuiaba-MT. For data collection, we used official documents from the State Department of Education Cuiaba-MT and documents two (02) schools, questionnaires, classroom observation and interviews. The data analysis indicates that the text produced in 2002 and the new texts produced in 2010 in public schools, are documents that are in constant process of interpretation and reinterpretation. And the schools surveyed, the documents express the way how is the recontextualization, presenting fragments reconstructed in the context of practice, blending between multiple conceptions cycle and designing curriculum, indicating that there is some conflict in the design planning education in the 2nd cycle by part of the teaching staff and teachers of science, with divergent discourses on the fundamentals of the proposed assessment on the 2nd cycle. The Regents Professors 2nd cycle develop their teaching approaches with the content and the textbook being the main guiding principle for the development of this practice. It was felt that the teaching strategy mobilized occurs through a transmissive approach and decontextualized the students' reality. Although the teachers make some approximations in their practice with the proposal of the cycles the way they structure their classes and mobilize indicate that in practice everyday curriculum of the school curriculum policy recontextualization occurs in the 2nd cycle.